Rene 41 Tensile Data - James, William Sean; Ganguly, Supriyo; Rodrigues Pardal, Goncalo (Cranfield University, 2022)
Tensile testing data of nickel superalloy Rene 41, manufactured using a plasma wire-arc directed energy deposition process.
Keywords: 'Rene 41'; 'nickel superalloys'; 'WAAM'; 'additive manufacturing'